DELIK ZINA DALAM PERSPEKTIF HUKUM ISLAM, KUHP DAN RKUHP - Jannah Matondang, Miftahul (Jurnal Landraad, 2022)
Abstract Adultery is increasingly becoming a trend in our society, this phenomenon can be seen from the increasing number of cases of abortion of fetuses resulting from illicit relationships. Adultery is also caused by the damage to the morality and spirituality of our young generation, the rise of promiscuity to the lack of supervision from parents. According to Islamic Sharia, adultery is sexual intercourse between a man and a woman without a valid marriage bond, with the threats of punishment for the perpetrators being: 1) if the perpetrator is married and commits adultery voluntarily, is not forced and is not raped, is by being whipped and stoned, 2) if the perpetrator is not married, then he is whipped with 100 lashes and exiled (locked up or imprisoned). While the definition of adultery according to the Criminal Code is voluntary sexual relations by someone who is married to someone who is not their husband or wife. Thus, adultery in the Criminal Code focuses on acts that injure a marriage, with a maximum penalty of nine months in prison, and new prosecutions can be made on complaints from tainted husbands or wives. Meanwhile, according to the RKUHP, the penalty for committing adultery is one year in prison and a maximum fine of ten million rupiah, with an absolute complaint offense which can only be prosecuted if there is a complaint from the husband, wife, parents or child who has been harmed.